Conservative treatment of interproximal incipient caries lesions by resin infiltration - Priscila Regis Pedreira (Brazilian Journal of Oral Sciences, 2021)
Minimally invasive dentistry is based on conservative techniques for the treatment of initial caries lesions, the so-called white spot lesions. One of the conservative maneuvers includes the use of enamel resin infiltrant: a low viscosity material that penetrates the enamel pores to stop lesion progression. Aim: Therefore, this case report aimed to describe the clinical case of a 28-year-old female patient under routine consultation, in which a radiographic examination showed the presence of two incipient caries lesions in the left upper premolars. Methods: The application of a resin infiltrating agent (Icon®, DMG – Hamburg, Germany) was chosen as treatment to stop caries lesions progression. Conclusion: The use of this conservative technique can be considered a promising approach for the prevention of dental tissue wear, and the resin infiltrant is considered an effective material.